(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Many Plant Protease inhibitors are found to have effects of tumor suppression in certain cell lines. In this work attempt has been made to determine anti-tumor/apoptotic property of trypsin inhibitor protein (WbTI2) from plant Psophocarpus tetragonolobus (L.)D.C. (winged bean) on human chronic myeloid leukemia cells (K562). Pure winged bean trypsin inhibitor protein was purified by affinity chromatography from recombinant molecule and human chronic myeloid leukemia cells were treated by it. Then viability of the treated cells were determined by simple microscopic study, MTT assay and flow cytometric analysis. All results revealed significant effect of WbTI2 on the viability of the human chronic myeloid leukemia cells. The IC50 value was determined to be 5µg/ml in MTT assay. The data was found to be statistically significant.